RELATED AND UNRELATED DIVERSIFICATION AND THEIR EFFECT ON HUMAN RESOURCE MANAGEMENT CONTROLS - Rowe, W. Glenn; Wright, Patrick M. (Strategic Management Journal, 1997)
This paper examines the link between related and unrelated diversification and human resource management (HRM) controls. The paper presents a model proposing that the type of corporate (macro) controls used by related or unrelated firms implies a relative emphasis on either flexibility or fit among HRM practices in that related firms emphasize flexibility and unrelated firms emphasize fit. This emphasis on flexibility or fit, in turn, has implications for the use of HRM (micro) controls such as clan, behavior, and outcome controls such that related firms exhibit the use of all three types of HRM controls, while unrelated firms exhibit a relative emphasis on the use of outcome controls. © 1997 by John Wiley & Sons, Ltd.